2011
DOI: 10.1182/blood-2010-12-327437
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of leukemia stem cells in chronic myelogenous leukemia patients in prolonged remission with imatinib treatment

Abstract: Imatinib mesylate treatment markedly reduces the burden of leukemia cells in chronic myelogenous leukemia (CML) patients. However, patients remain at risk for relapse on discontinuing treatment. We have previously shown that residual BCR-ABL ؉ progenitors can be detected in CML patients within the first 2 years of imatinib treatment. However, reduced rates of relapse and continued decline of BCR-ABL levels with prolonged treatment, together with the ability of selected patients to maintain remission after dis-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
187
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(200 citation statements)
references
References 30 publications
11
187
0
2
Order By: Relevance
“…Nonetheless second and third generation TKIs have been developed in response to BCR-ABL mutations inferring resistance to treatment (for review see O'Hare 21 ). Despite continued TKI therapy in CML patients, the minimal effect of TKIs on primitive CML haemopoietic cells results in the persistence of minimal residual disease (MDR) which causes disease relapse upon drug withdrawal [22][23][24][25][26][27] . Given that CML is a stem-cell-driven disease, any new potentially curative therapies must be tested on primary stem cells, which are only available in finite quantities.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless second and third generation TKIs have been developed in response to BCR-ABL mutations inferring resistance to treatment (for review see O'Hare 21 ). Despite continued TKI therapy in CML patients, the minimal effect of TKIs on primitive CML haemopoietic cells results in the persistence of minimal residual disease (MDR) which causes disease relapse upon drug withdrawal [22][23][24][25][26][27] . Given that CML is a stem-cell-driven disease, any new potentially curative therapies must be tested on primary stem cells, which are only available in finite quantities.…”
Section: Introductionmentioning
confidence: 99%
“…1 The introduction of ABL TK inhibitors (TKI) has dramatically changed the management of newly diagnosed chronic phase (CP) CML patients, with the vast majority now achieving deep molecular responses, while enjoying a good quality of life. 2 However, 15% to 20% of patients show variable degrees of resistance to currently available TKI, 3 and even in patients achieving deep responses, including those with undetectable BCR-ABL transcript levels, there is evidence of persistence of BCR-ABL 1 cells at the stem-cell level 4,5 and of positivity for BCR-ABL genomic DNA by polymerase chain reaction (PCR). 6,7 Furthermore, over 50% of patients achieving sustained undetectable BCR-ABL transcript levels showed evidence of molecular relapse upon TKI discontinuation.…”
Section: Introductionmentioning
confidence: 99%
“…The second recent argument for stem cell persistence in CML has been obtained in patients in complete molecular response (BCR-ABL undetectable in peripheral blood) and in whom the IM therapy has been stopped: In a cohort of 100 patients, the discontinuation of IM therapy led to relapse in 61% of cases (16) whereas the remainder of the patient population remained BCR-ABL-negative in their peripheral blood. These patients might be operationally "cured" of their leukemia but recently it has been shown that BCR-ABL-expressing LSC persist in the marrow of CML patients in complete molecular response, on or off TKI therapies (17,18). The long-term dormancy of CML stem cells is a phenomenon which is probably very common and poorly understood.…”
Section: Stem Cell Persistence and Long-term Dormancymentioning
confidence: 99%